Developmentally restricted immunoglobulin heavy chain variable region gene expressed at high frequency in chronic lymphocytic leukemia. - Kipps, T J (1989)
During fetal development, murine and human B-lineage cells rearrange and express a highly restricted set of immunoglobulin heavy chain variable region genes (VH genes). We noted that a VH gene of the restricted human fetal repertoire, designated 51p1, potentially could encode the VH region of two human IgM rheumatoid factor proteins. These rheumatoid factors share a cross-reactive idiotype (CRI) defined by reactivity with G6, a murine monoclonal antibody that recognizes an antibody heavy chain determinant present on many human IgM autoantibodies, particularly rheumatoid factors. Recently, we found that the G6 CRI also is expressed frequently by neoplastic CD5 (Leu1) B cells from patients with chronic lymphocytic leukemia (CLL) or small lymphocytic lymphoma. However, neoplastic CD5-negative B cells from patients with lymphomas of follicular center cell origin rarely express this CRI. Here, we report that G6-reactive leukemic cells from two unrelated CLL patients express a VH gene that shares greater than 99% homology with a rearranged VH gene previously isolated from the leukemic cell DNA of another CLL patient and that is identical to VH 51p1. Using the polymerase chain reaction, we find that this VH gene is rearranged, and presumably expressed, in the genomic DNA of all examined cases of G6-reactive CLL or small lymphocytic lymphoma. Thus these data indicate that the autoantibody-associated G6 CRI is a serologic marker for a conserved and developmentally restricted VH1 gene that is expressed at high frequency in CD5 B-cell malignancies and early B-cell ontogeny.